2006
DOI: 10.1029/2005gc000977
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol iron and aluminum solubility in the northwest Pacific Ocean: Results from the 2002 IOC cruise

Abstract: [1] Dust aerosol samples were collected across the western North Pacific Ocean during May-June 2002. Samples were analyzed for soluble aerosol Fe(II), Fe(II) + Fe(III), and Al as well as major cations and anions. The aerosol samples were leached using a 10 second exposure to either filtered surface seawater or ultrapure deionized water yielding a measure of the ''instantaneous'' soluble fraction. A variety of analytical methods were employed, including 57 Fe isotope dilution high-resolution ICP-MS, energy disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
222
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(243 citation statements)
references
References 39 publications
18
222
2
1
Order By: Relevance
“…For example, applying a sequential leach method to the aerosol samples used in this study, Shelley et al [54] found the Sol Al obtained using the acetic acid (pH 2) hydroxylamine hydrochloride ('acetate') leach of Berger et al [55] to be about an order of magnitude greater than for the same samples using the instantaneous deionized water ('DI') leach of Buck et al [56]. For the stations between Africa and the Cape Verde Islands, Sol Al obtained using the acetate leach averaged about 10% while Sol Al determined using the DI leach varied between 0.3% and 1.0%.…”
Section: (A) Aerosol Depositionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, applying a sequential leach method to the aerosol samples used in this study, Shelley et al [54] found the Sol Al obtained using the acetic acid (pH 2) hydroxylamine hydrochloride ('acetate') leach of Berger et al [55] to be about an order of magnitude greater than for the same samples using the instantaneous deionized water ('DI') leach of Buck et al [56]. For the stations between Africa and the Cape Verde Islands, Sol Al obtained using the acetate leach averaged about 10% while Sol Al determined using the DI leach varied between 0.3% and 1.0%.…”
Section: (A) Aerosol Depositionmentioning
confidence: 99%
“…In this context, thorium has an advantage because one isotope ( 232 .3)) using measured dissolved 232 Th inventories and estimates of aerosol Th solubility based on (a) the instantaneous deionized water leach (DI, [56]) and (b) the acetate-reducing agent leach (acetate, [55]). In each case, the residence time of Th is derived from the 234 U-230 Th radioactive disequilibrium integrated from the surface to the depth to which the 232 Th inventory is integrated (either 50 m or 500 m).…”
Section: (A) Aerosol Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical flow rates were 20-30 L min -1 per filter, giving total sample volumes of 50-100 m 3 . Samples were stored frozen (-20 °C) until analysis in the UK, as storage at aerosol solubility decreases when stored at room temperature (Buck et al, 2006) .…”
Section: Aerosol Sampling Chemical and Physical Characterization 27mentioning
confidence: 99%
“…In addition, the metal composition was characterized from the size segregated aerosol samples using total reflection X-ray fluorescence spectrometry (TXRF, Bruker AXS, Germany) (Müller et al, 2010 fraction of metals and nutrients in the samples. 100 ml of ultrapure water was passed through the filter using a filtration apparatus and a small vacuum pump (Buck et al, 2006). The resulting filtrate was analysed for nutrients (NO 3 -, NH 4 + , PO 4 3-, DOC, DON) using a standard nutrient autoanalyser, anions (Cl -and SO 4 2-) using ion chromatography, high temperature combustion TOC-TDN analyser (TOC-V-CPN, Shimadzu), and a broad suite of metals measured using ICP-MS (Thermo, X-series).…”
Section: Chemical Aerosol Analysismentioning
confidence: 99%